Digital Media and Cultural Transformation: Rethinking Communication in Networked Societies - Mulyaningsih Mulyaningsih; Daniel Meier; Shofiyatul Azmi (Journal of Humanities Research Sustainability, 2026)
Background. Digital media has transformed the way societies communicate, interact, and perceive culture. The rise of networked communication platforms has reshaped social structures, altered cultural practices, and influenced global connections. This transformation presents a new set of challenges and opportunities for understanding how communication works in an increasingly digital world. As networked societies evolve, it is crucial to examine how digital media affects cultural production, distribution, and consumption, as well as the implications for social interaction and identity. Purpose. The objective of this research is to explore the role of digital media in cultural transformation, focusing on how networked communication platforms reshape communication practices, cultural identities, and social dynamics. The study aims to identify the ways digital media influences cultural norms and values, examining both the positive and negative aspects of these transformations. Method. This study employs a qualitative approach, utilizing a combination of content analysis and case studies. Key examples of digital media platforms and their impact on communication practices are analyzed, including social media, blogs, and digital video content. Results. The research finds that digital media plays a dual role in cultural transformation, facilitating both the globalization of culture and the emergence of new, localized cultural expressions. Networked communication platforms serve as spaces for the negotiation of identities, community-building, and the dissemination of cultural norms. Conclusion. The research concludes that digital media is a powerful agent of cultural transformation, influencing communication, identity formation, and social practices. It highlights the need for a nuanced understanding of these shifts in the context of networked societies.